Three-dimensional model reconstruction of pipeline with inner wall corrosion based on ultrasonic phased array technology - Yulong ZHANG; Rongguo HOU; Rui WANG; Miaomiao ZHANG; Zhe LYU (You-qi chuyun, 2023)
The inner wall corrosion of pipelines is concealed and hard to monitor in time. In order to visualize the shape of the internally corroded pipeline, as well as the defect volume and its spatial distribution, a three-dimensional (3D) model reconstruction method based on the ultrasonic phased array technology was proposed for the internally corroded pipeline. A self-built acquisition platform was used to control the one-dimensional linear array probes for the phased array, and the reflected echo signal was used to obtain the space coordinates between the inner and outer diameters of the corroded pipeline. Then, the point cloud data set between the inner and outer diameters was constructed by the interpolation method, and the point cloud data of each fracture zone were obtained by the hierarchical scanning method. Besides, data processing, reverse model reconstruction and forward modeling were performed for the 3D model reconstruction of the collected point cloud data. Finally, the reconstructed 3D model was compared with the point cloud data obtained by the Creaform 3D laser scanner. The results show that it is feasible to obtain the point cloud data using one-dimensional linear array probes based on the ultrasonic phased array technology, and the established 3D model and defects have small errors and high precision, which has important reference value for the safety evaluation of oil and gas pipelines.